Antituberculosis drug-induced hepatotoxicity: a comparison between patients with and without human immunodeficiency virus seropositivity - Coca,Natalia Saldanha Magalhães (2010)
INTRODUCTION: The prevalence and risk factors for rifampin, isoniazid and pyrazinamide hepatotoxicity were evaluated in HIV-infected subjects and controls. METHODS: Patients with tuberculosis (30 HIV positive and 132 HIV negative), aged between 18 and 80 years-old, admitted to hospital in Brazil, from 2005 to 2007, were selected for this investigation. Three definitions of hepatotoxicity were used: I) a 3-fold increase in the lower limit of normal for alanine-aminotransferase (ALT); II) a 3-fold increase in the upper limit of normal (ULN) for ALT, and III) a 3-fold increase in the ULN for ALT plus a 2-fold increase in the ULN of total bilirubin. RESULTS: In groups with and without HIV infection the frequency of hepatotoxicity I was 77% and 46%, respectively (p < 0.01). Using hepatotoxicity II and III definitions no difference was observed in the occurrence of antituberculosis drug-induced hepatitis. Of the 17 patients with hepatotoxicity by definition III, 3 presented no side effects and treatment was well tolerated. In 8 (36.4%) out of 22, symptoms emerged and treatment was suspended. Alcohol abuse was related to hepatotoxicity only for definition I. CONCLUSIONS: Depending on the definition of drug-induced hepatitis, HIV infection may or may not be associated with hepatotoxicity. The impact that minor alterations in the definition had on the results was impressive. No death was related to drug-induced hepatotoxicity. The emergence of new symptoms after initiating antituberculosis therapy could not be attributed to hepatotoxicity in over one third of the cases.